The Relationship between HbA1c and Glucosuria in Diabetes Mellitus (DM) Patients: Hubungan HbA1c dengan glukosuria Pada Penderita Diabetes Mellitus (DM) - Nurjanah, Mutia Hariani; Wijaya, Anas Fadli; Meri, Meri; Tilarso, Dara Pranidya; Siswidiani, Maya Diva (Universitas Muhammadiyah Sidoarjo, 2023)
Diabetes mellitus is a condition of abnormalities in blood glucose metabolism that can cause various macroangiopathy complications such as disorders of the peripheral blood vessels, heart blood vessels, cerebral blood vessels as well as microangipathic complications such as diabetic retinopathy disorders, nephropathy and neuropathy. HbA1c describes the level of sugar in the blood for the last 3 months. Glucose is not found in normal urine because it is reabsorbed back into the blood vessels by renal filtration. The aim of this study was to determine the relationship between HbA1c levels and glucosuria in people with diabetes mellitus. The design of this study is a cross-sectional approach to DM patients. The sampling technique used was purposive sampling. Data analysis was carried out by means of Spearman's rank correlation test. Results Correlation analysis showed that there was a significant relationship between HbA1c levels and glucosuria in DM patients p-value 0.005 with a coefficient value of 0.597. The conclusion from this study is that there is a significant relationship with a strong correlation strength and a positive correlation direction for DM sufferers.